2022
DOI: 10.1038/s12276-022-00735-x
|View full text |Cite
|
Sign up to set email alerts
|

The m6A reader IGF2BP3 promotes acute myeloid leukemia progression by enhancing RCC2 stability

Abstract: N6-methyladenosine (m6A) is the most abundant posttranscriptional modification of mRNA in eukaryotes. Recent evidence suggests that dysregulated m6A-associated proteins and m6A modifications play a pivotal role in the initiation and progression of diseases such as cancer. Here, we identified that IGF2BP3 is specifically overexpressed in acute myeloid leukemia (AML), a subtype of leukemia associated with poor prognosis and high genetic risk. IGF2BP3 is required for maintaining AML cell survival in an m6A-depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 39 publications
2
52
0
Order By: Relevance
“…In this study, we found the treatment of 3-nitropropionic acid (3-NP), a mitochondrial toxin inducing intracellular OS by targeting complex II of electron transport chain, led to significant downregulation of Insulin-like growth factor 2 mRNA-binding protein 1 (IGF2BP1) and subsequently resulted in MDM2 mRNA instability in GCs. IGF2BP1 is an RNA-binding protein which preferentially binds to m 6 A modifications and helps to stabilize its targeted transcripts [ [15] , [16] , [17] , [18] ]. As a potent oncogenic factor, IGF2BP1 regulates proliferation, cell cycle progression and stemness of cancer cells [ 17 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we found the treatment of 3-nitropropionic acid (3-NP), a mitochondrial toxin inducing intracellular OS by targeting complex II of electron transport chain, led to significant downregulation of Insulin-like growth factor 2 mRNA-binding protein 1 (IGF2BP1) and subsequently resulted in MDM2 mRNA instability in GCs. IGF2BP1 is an RNA-binding protein which preferentially binds to m 6 A modifications and helps to stabilize its targeted transcripts [ [15] , [16] , [17] , [18] ]. As a potent oncogenic factor, IGF2BP1 regulates proliferation, cell cycle progression and stemness of cancer cells [ 17 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, VIRMA, which plays an oncogenic role in multiple human cancers ( Zhu et al, 2021 ), was more highly expressed in m6Acluster A compared with the other two clusters. Another gene with relatively higher expression in m6Acluster A-IGF2BP3-was recently found to be specifically overexpressed in AML and contributes to tumorigenesis and poor prognosis of this disease ( Zhang et al, 2022 ). These findings agreed favorably with the observed negative prognostic influence of m6Acluster A.…”
Section: Resultsmentioning
confidence: 99%
“…Methylation of N6 adenosine (m6A), which has been discovered as reversible RNA methylation affecting the regulation of post-transcriptional gene expression programs and protein production, is one of the most abundant internal marks on mammalian mRNA (Desrosiers et al, 1974;Fu et al, 2014;Zhao et al, 2017;Shi et al, 2019). The biological functions altered by m6A modifications are dynamically controlled by the m6A methyltransferase complex (writers), m6A demethylases (erasers), and m6A-binding proteins (readers) (Shi et al, 2019;Zaccara et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…FTO promoted leukemia oncogene mediated cell transformation and leukemia by reducing m6A levels in mRNA transcripts, inhibited all-trans retinoic acid (ATRA) induced AML cell differentiation, and modulated the expression of its target genes such as retinoic acid receptor alpha (RARA) and ankyrin repeat and SOCS box containing 2 (ASB2) ( 132 ). It has also been demonstrated that IGF2BP3 is required to maintain the survival of AML cells in an m6A-dependent manner and that IGF2BP3 functions to promote AML progression by interacting with RCC2 mRNA and stabilizing the expression of m6A-modified RNA ( 133 ). Studies have shown that overexpression of YTHDF2 in AML cells causes decreased half-life of a wide range of m6A transcripts, including TNF receptor superfamily member 2 (TNFRSF2) transcripts, which could help maintain the function of leukemic stem cells, and enhanced hematopoietic stem cell activity when YTHDF2 is knocked down ( 134 ).…”
Section: M6a Modification and Solid Tumorsmentioning
confidence: 99%